Information Technology and Politics of Incorporation - Markussen, Randi; Olesen, Finn (Outlines. Critical Practice Studies, 2001)
Information technologies (IT) have become a politically important issue over the last ten years. Governmental reports promote the idea of a new information society, or network society, where ITs are a prerequisite for the economic and social development. The discourse and the rhetoric about technology and its relation to society are dominated by modern, rational and macrosocial understandings of technology. In this paper we challenge dominant rational discourses on technology and present alternative views to bring new perspectives to the subject in order to complicate and enrich our understanding of technology and how it relates to society. Our aim is to develop a theoretical framework that can account for a dynamic and microsocial approach to studying the implementation of an Electronic Patient Record (EPR) at a Danish hospital. The key notions in the framework are 'trading zone', 'cooperation' and 'technological translations'.